2021
DOI: 10.3390/antibiotics10070801
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Multidrug Resistance Staphylococci in Shelter Dogs in Timisoara, Romania

Abstract: The present study aimed to determine the prevalence of Staphylococcus species, which pose risks for public health, by evaluating skin samples collected from dogs in an animal shelter in Timisoara. Skin samples were taken from 78 dogs, which were either clinically healthy or suffering from dermatological conditions. Staphylococcus spp. was isolated and recognized based on conventional methods based on colony appearance, microscopic morphology, sugar fermentation, and coagulase activity. Following biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In our study, the frequency of S. aureus and MRSA in hunting dogs was 15.4% and 9%, respectively. János et al also reported similar results with a frequency of S. aureus and MRSA of 11.62% and 9.30%, respectively, in kennel dogs from Romania [ 43 ]. Other studies have reported a lower prevalence of MRSA in dogs [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 56%
“…In our study, the frequency of S. aureus and MRSA in hunting dogs was 15.4% and 9%, respectively. János et al also reported similar results with a frequency of S. aureus and MRSA of 11.62% and 9.30%, respectively, in kennel dogs from Romania [ 43 ]. Other studies have reported a lower prevalence of MRSA in dogs [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 56%
“…In another investigation, a total of 12.8% of the screened milk and dairy products origin S. aureus isolates were MDR [ 21 ]. In addition, in context of the One Health approach, the recorded worrying 100% MDR pattern in case of S. aureus strains isolated from shelter dogs with skin lesions from Timișoara Municipility, included in the monitored Banat region in the present study, indirectly suggests the increased AMR trend in the case of this pathogen in Romania [ 31 ]. In contrast, in a study conducted in Poland most of the isolates (47.5%) were found to be resistant to only one antimicrobial [ 11 ].…”
Section: Discussionmentioning
confidence: 87%
“…It is important to mention that the acquiring of VAN resistance in the case of S. aureus can be closely related to the presence of the vanA gene clusters and several mobile genetic elements (e.g., self-transferable or mobilizable plasmids, conjugative transposons) in other Gram-positive bacteria (e.g., Enterococcus faecalis , E. faecium , Clostidium difficile ) [ 34 ]. Until now, VAN resistance has not been reported for food origin S. aureus strains in Romania, but its occurrence has been recently confirmed for strains isolated from shelter dogs with skin lesions [ 31 ]. Further molecular studies focusing on the evidence of the van A gene in a large number of food or animal origin S. aureus isolates are still required to improve our understanding about the demonstrated spreading of VAN resistance by this pathogen in Romania.…”
Section: Discussionmentioning
confidence: 99%
“…Its use appears to be a cost-effective and effective treatment, with no side effects [7]. Staphylococcus aureus is an common bacteria that cause disease in dogs and is thought to be a reservoir for drug-susceptible and drugresistant bacteria such as S. aureus [8,9]. This has led to the development of new alternative treatments, one of which is ethanolic extracts of propolis for topical applications, which have proven to be effective and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…All Staphylococcus species that cause infections in humans and domestic animals can develop resistance to antibiotics [8][9][10][11]. The predisposition for staphylococci to develop antimicrobial resistance is a cause of major concern in both human and veterinary medicine [12,13].…”
Section: Introductionmentioning
confidence: 99%